ANALISIS TERHADAP MANAJEMEN DANA MUDHARABAH DALAM PERBANKAN SYARI’AH - Ghofur, Abdul (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2016)
This study tried to the analyze practices mudharabah fund management in Islamic banking from the perspective of normative and philosophical. Mudharabah is interesting to examine, because the beginning of a substitute interest (riba) is the contract of profit sharing, one of which is based on mudharabah. Mudharabah is also rated as the contract representing equity in the transaction. However, in reality, the application of this mudharabah is not so simple, there are some problems inside it. The research found some results, among other things: First, the contract of mudharabah is one of contracts that is used by the Islamic bank to manage the funding and financing in order to avoid the practice of interest (riba). Second, ideally, mudharabah becone the mainstay products of Islamic banking, both in terms of funding or financing. Because, with the principle of partnership, the two parties are equally benefited. Thirdly, in fact, the bank and the customer will not want for various losses. While the mudharabah practice allows for this. Therefore, it requires tactical steps to minimize the impact of such losses. One of these steps is to conduct the training to prospective mudharib intensively for in terms of professionalism and confidence (trust) it. Further, it requires accompaniment for the candidate of capital manager (mudharib).